Networked Sensor - Aided Tracking of Walking Human in Robotic Space. (17th January 2013) - Jin, Taeseok
The robots that will be needed in the near future are human-friendly robots that are able to coexist with humans and support humans effectively. To realize this, it is necessary for a robot to carry out human tracking as one of its human-affinitive movements. In this research, a predictable robotic space is introduced in order for a robot to follow a walking human by the shortest time trajectory. The mobile robot is controlled to follow the walking human using distributed networked sensors. The moving object is assumed to be a point-object and projected onto an image plane to form a geometrical constraint equation that provides position data of the object based on the kinematics of the robotic space. The computer simulation and experimental results on the mobile robot's success in estimating information and following a walking human are presented.